MODERN APPROACHES TO INCREASING THE EFFICIENCY OF COMMERCIAL BANKS BRANCHES: THE EXPERIENCE OF UZBEKISTAN - Nuratdinova Aysha (Modern American Journals, 2025)
This article analyzes modern approaches aimed at improving the efficiency of commercial bank branch operations in the Republic of Uzbekistan. In the context of the growing banking services market, the article examines opportunities to achieve efficiency through optimized management models, digitalization, customer-oriented services, and innovative technologies. Additionally, practical suggestions based on national experience are developed.
Keywords: Commercial bank, branch network, efficiency, digitalization, banking services, management, Uzbekistan experience.